U.S. nuclear weapons policy : confronting today's threats - Bunn, George, 1925-; Chyba, Christopher F.; Perry, William James, 1927- (Center for International Security and Cooperation, Freeman Spogli Institute for International Studies, Stanford, Calif. ; Brookings Institution Press, 2006)
What role should nuclear weapons play in todays world? How can the United States promote international security while safeguarding its own interests? U.S. Nuclear Weapons Policy informs this debate with an analysis of current nuclear weapons policies and strategies, including those for deterring, preventing, or preempting nuclear attack; preventing further proliferation, to nations and terrorists; modifying weapons designs; and revising the U.